2000
DOI: 10.1103/physrevd.62.105013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental bounds on masses and fluxes of nontopological solitons

Abstract: We have re-analyzed the results of various experiments which were not originally interested as searches for the Q-ball or the Fermi-ball. Based on these analyses, in addition to the available data on Q-balls, we obtained rather stringent bounds on flux, mass and typical energy scale of Q-balls as well as Fermi-balls. In case these nontopological solitons are the main component of the dark matter of the Galaxy, we found that only such solitons with very large quantum numbers are allowed. We also estimate how se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 43 publications
(89 reference statements)
2
90
0
Order By: Relevance
“…This is the basis for the Q-ball detections. 18,19) The cross section for KKST process is given by the geometrical one, and M F $ 5 Â 10 2 GeV is allowed. Notice that the dark matter Q balls with larger charges can be detected by the future experiments such as Telescope Array Project or the OWL-AIRWATCH detector.…”
Section: Q-ball Detectionmentioning
confidence: 99%
“…This is the basis for the Q-ball detections. 18,19) The cross section for KKST process is given by the geometrical one, and M F $ 5 Â 10 2 GeV is allowed. Notice that the dark matter Q balls with larger charges can be detected by the future experiments such as Telescope Array Project or the OWL-AIRWATCH detector.…”
Section: Q-ball Detectionmentioning
confidence: 99%
“…One particular model of Q-ball interactions predicts that mica detectors are also sensitive to Q-balls with Z Q ≥ 10 [373]. Based on such an interpretation, the nuclearite flux limits from ancient mica mentioned above can also be applied to Q-balls of roughly the same masses.…”
Section: Ancient Micamentioning
confidence: 98%
“…However, energy loss predictions strongly depend on Q-ball properties other than the mass (such as electric charge Z Q ) and on model assumptions (e.g., SUSY hypotheses), making the interpretation more difficult. Within one particular model of Q-ball interactions, it was found that CR39 nuclear-track detectors are sensitive to Z Q ≥ 3 [373]. Based on such an interpretation, the nuclearite flux limits from MACRO, OHYA and SLIM mentioned above can also be applied to Q-balls of roughly the same masses.…”
Section: Plastic Nuclear-track Detectorsmentioning
confidence: 99%
“…Observational signatures of SUSY Q-balls has been studied [12], and their mass and flux were constrained by experimental data of the searches for magnetic monopoles and heavy cosmic rays [13]. Currently direct searches for neutral Q-balls and for electrically charged Q-balls are in progress in Super-Kamiokande II [14] and in the SLIM Experiment [15], respectively.…”
Section: Introductionmentioning
confidence: 99%